Studies on electrical properties of Fe doped ZnO nanostructured oxides synthesized by sol–gel method. (October 2021) - Lehru, Rujuta; Radhanpura, Jaydeep; Kumar, Ramesh; Zala, Divyarajsinh; Vadgama, V.S.; Dadhich, Himanshu; Rathod, V.R.; Trivedi, R.K.; Pandya, D.D.; Shah, N.A.; Solanki, P.S.
Abstract: We report the results of the studies on electrical properties of Zn1–x Fex O (x = 0.10, 0.15 and 0.20) nanoparticles synthesized using sol–gel method. X–ray diffraction (XRD) measurement confirms the presence of extra phase of ZnFe2 O4 in all the samples which gets enhanced with increase in Fe concentration. Surface morphological studies using atomic force microscopy (AFM) suggest the reduction in grain size with increase in Fe doping level in ZnO. All the dielectric parameters show dispersion nature and dielectric constant has been found to increase with Fe content. The obtained dielectric behavior has been understood on the basis of Maxwell–Wagner (M − W) mechanism and Koop's theory. Frequency dependent electrical conductivity has been understood on the basis of Jonscher's universal power law that suggests a conduction of charge carrier through correlated barrier hopping (CBH) mechanism. Impedance spectroscopy measurements have been explained on the basis of crystal cores and crystal boundary density. Grain boundary contribution in conduction mechanism is identified by fitting equivalent circuit model on cole–cole plots. Temperature and magnetic field dependent variation in electrical properties of studied samples has been understood on the basis of structure–property correlations. Highlights: Cost effective synthesis of Fe doped ZnO nanoparticles using sol–gel method. Substitutional effect of Fe on electrical properties of Zn1–x Fex O nanoparticles. Crystallinity degradation due to substitution of Fe by Zn in ZnO lattice. Fe doping induced improved dielectric behavior of Zn1–x Fex O nanoparticles. Understanding of mechanisms responsible for electrical behaviors Zn1–x Fex O nanoparticles.